Staphylococci isolated from cats in Italy with superficial pyoderma and allergic dermatitis: Characterisation of isolates and their resistance to antimicrobials. Issue 1 (11th October 2022) - Cavana, Paola; Robino, Patrizia; Stella, Maria Cristina; Bellato, Alessandro; Crosaz, Odile; Fiora, Sara Rebecca; Nebbia, Patrizia
Abstract: Background: In cats, superficial pyoderma traditionally is considered rare and few reports are available. There is a particular lack of studies concerning Staphylococcus species associated with pyoderma in subjects affected by allergic skin diseases. Hypothesis/objectives: (i) To evaluate the association between Staphylococcus spp. and superficial pyoderma in allergic cats and (ii) to characterise isolated staphylococci and analyse their antimicrobial resistance patterns. Animals: Forty‐one cats with allergic dermatitis and superficial pyoderma in Italy. Materials and Methods: Skin swabs were cultured for the isolation of Staphylococcus spp. Species identification was performed by matrix‐assisted laser desorption/ionisation time of flight mass spectrometry and 16S ‐rRNA sequencing. Staphylococcus aureus isolates were further characterised by staphylococcal protein A gene‐typing. Antimicrobial susceptibility was performed by the disk diffusion method. Results: Staphylococci were isolated from 36/41 cats sampled and 39 different isolates were identified. Uneven distribution of staphylococcal species was observed among different body locations. The 39 isolates were S. aureus (n = 15), S. felis (n = 10), S. pseudintermedius (n = 8) and other staphylococci (n = 6). Eight different S. aureus spa ‐types associated with human clonal complexes were identified. Antimicrobial resistance was observed to penicillin (56.4%), tetracycline (46.2%), enrofloxacin (33.3%), erythromycin (28.2%), amikacin (25.6%), clindamycin (23.1%), marbofloxacin (15.4%), gentamicin (12.8%), trimethoprim‐sulfamethoxazole (10.3%), chloramphenicol (7.7%) and cefoxitin/oxacillin (5.1%). Fifteen isolates (38.4%) were multidrug‐resistant while meticillin resistance was associated only with S. pseudintermedius . Conclusions and Clinical Relevance: These results confirm that S. aureus, S. pseudintermedius, and S. felis are frequently associated with superficial pyoderma in allergic cats. Semi‐synthetic penicillins remain a suitable first‐line treatment in this study, yet the high prevalence of antimicrobial resistant isolates suggests that antimicrobial susceptibility testing should be performed routinely. Abstract : Background – In cats, superficial pyoderma traditionally is considered rare and few reports are available. There is particular lack of studies concerning Staphylococcus species associated with pyoderma in subjects affected by allergic skin diseases. Hypothesis/objectives – (i) to evaluate the association between Staphylococcus spp. and superficial pyoderma in allergic cats in Italy and (ii) to characterise isolated staphylococci and analyse their resistance patterns. Conclusions and clinical relevance – These results confirm that S. aureus, S. pseudintermedius and S. felis are frequently associated with superficial pyoderma in allergic cats. Semi‐synthetic penicillins remain a suitable first‐line treatment, yet the high prevalence of resistance suggests that antimicrobial susceptibility testing should be performed routinely. Résumé: Contexte: Chez les chats, la pyodermite superficielle est traditionnellement considérée comme rare et peu de publications sont disponibles. On manque notamment d'études concernant les espèces de Staphylococcus associées à la pyodermite chez les sujets atteints de dermatoses allergiques. Hypothèse/objectifs: (i) évaluer l'association entre Staphylococcus spp. et pyodermite superficielle chez les chats allergiques ; et (ii) caractériser les staphylocoques isolés et analyser leurs profils de résistance aux antimicrobiens. Animaux: Quarante et un chats atteints de dermatite allergique et de pyodermite superficielle en Italie. Matériels et méthodes: Des écouvillons cutanés ont été utilisés pour l'isolement de Staphylococcus spp. L'identification des espèces a été réalisée par spectrométrie de masse et séquençage de l'ARNr 16S. Les isolats de S. aureus ont ensuite été caractérisés par le typage du gène de la protéine A staphylococcique. La sensibilité aux antimicrobiens a été réalisée par la méthode de diffusion sur disque. Résultats: Des staphylocoques ont été isolés chez 36/41 chats échantillonnés et 39 isolats différents ont été identifiés. Une répartition inégale des espèces de staphylocoques a été observée entre les différentes localisations corporelles. Les 39 isolats étaient S. aureus ( n = 15), S. felis ( n = 10), S. pseudintermedius ( n = 8) et d'autres staphylocoques ( n = 6). Huit différents types de S. aureus spa associés à des complexes clonaux humains ont été identifiés. Une résistance antimicrobienne a été observée à la pénicilline (56, 4 %), la tétracycline (46, 2 %), l'enrofloxacine (33, 3 %), l'érythromycine (28, 2 %), l'amikacine (25, 6 %), la clindamycine (23, 1 %), la marbofloxacine (15, 4 %), la gentamicine (12, 8 %), triméthoprime‐sulfaméthoxazole (10, 3 %), chloramphénicol (7, 7 %) et céfoxitine/oxacilline (5, 1 %). Quinze isolats (38, 4 %) étaient multirésistants tandis que la résistance à la méticilline n'était associée qu'à S. pseudintermedius . Conclusions et pertinence clinique: Ces résultats confirment que S. aureus, S. pseudintermedius et S. felis sont fréquemment associés à des pyodermites superficielles chez les chats allergiques. Les pénicillines semi‐synthétiques restent un traitement de première ligne approprié dans cette étude, mais la forte prévalence d'isolats résistants aux antimicrobiens suggère que les tests de sensibilité aux antimicrobiens doivent être effectués systématiquement. Resumen: Introducción: en los gatos, la pioderma superficial tradicionalmente se considera rara y hay pocos informes disponibles. Existe una falta particular de estudios sobre especies de Staphylococcus asociadas con pioderma en sujetos afectados por enfermedades alérgicas de la piel. Hipótesis/objetivos: (i) evaluar la asociación entre Staphylococcus spp . y pioderma superficial en gatos alérgicos; y (ii) caracterizar estafilococos aislados y analizar sus patrones de resistencia antimicrobiana. Animales: cuarenta y un gatos con dermatitis alérgica y pioderma superficial en Italia. Materiales y Métodos: Se cultivaron hisopos de piel para el aislamiento de Staphylococcus spp . La identificación de especies se realizó mediante espectrometría de masas de tiempo de vuelo de desorción/ionización láser asistida por matriz y secuenciación de 16S‐rRNA. Los aislados de S. aureus se caracterizaron además mediante la tipificación del gen de la proteína A estafilocócica. La susceptibilidad antimicrobiana se realizó por el método de difusión en disco. Resultados: Se aislaron estafilococos de 36/41 gatos muestreados y se identificaron 39 aislamientos diferentes. Se observó una distribución desigual de las especies de estafilococos entre las diferentes ubicaciones del cuerpo. Los 39 aislamientos fueron S. aureus ( n = 15), S. felis ( n = 10), S. pseudintermedius ( n = 8) y otros estafilococos ( n = 6). Se identificaron ocho tipos diferentes de S. aureus spa asociados con complejos clonales humanos. Se observó resistencia antimicrobiana a penicilina (56, 4 %), tetraciclina (46, 2 %), enrofloxacina (33, 3 %), eritromicina (28, 2 %), amikacina (25, 6 %), clindamicina (23, 1 %), marbofloxacina (15, 4 %), gentamicina (12, 8 %). %), trimetoprima‐sulfametoxazol (10, 3%), cloranfenicol (7, 7%) y cefoxitina/oxacilina (5, 1%). Quince aislamientos (38, 4%) fueron multirresistentes, mientras que la meticilina se asoció solo con S. pseudintermedius . Conclusiones y relevancia clínica: Estos resultados confirman que S. aureus, S. pseudintermedius y S. felis se asocian frecuentemente con pioderma superficial en gatos alérgicos. Las penicilinas semisintéticas siguen siendo un tratamiento de primera línea adecuado en este estudio, aunque la alta prevalencia de aislados resistentes a los antimicrobianos sugiere que las pruebas de susceptibilidad a los antimicrobianos deben realizarse de forma rutinaria. Zusammenfassung: Hintergrund: Bei Katzen ist eine oberflächliche Pyodermie traditionell eher eine Rarität und es gibt wenige Publikationen darüber. Es fehlen vor allem Studien in Bezug auf die Staphylcoccus Spezies bei einer Pyodermie bei Patienten mit allergischer Hauterkrankung. Hypothese/Ziele: (i) eine Evaluierung des Zusammenhangs zwischen Staphylcoccus spp. und oberflächlicher Pyodermie bei allergischen Katzen; und (ii) eine Charakterisierung der isolierten Staphylococci und eine Analyse des antimikrobiellen Resistenzmusters. Materialien und Methoden: Von Hauttupfern wurden Kulturen zur Isolierung von Staphylcoccus spp. angelegt. Es wurde eine Spezies Identifizierung mittels Matrix‐unterstützter Laser Desorption Ionisierung, Flugzeitmassenspektrometrie und 16S ‐rRNA Sequenzierung durchgeführt. S. aureus Isolate wurden weiters durch Staphylokokken Protein A Gen‐Typisierung charakterisiert. Die antimikrobielle Empfindlichkeit wurde mittels Disk Diffusionsmethode bestimmt. Ergebnisse: Staphylokokken wurden von 36/41 Katzenproben isoliert und 39 verschiedene Isolate wurden identifiziert. Eine unterschiedliche Verteilung der Staphylokokken Spezies wurde an den verschiedenen Körperstellen beobachtet. Die 39 Isolate waren S. aureus ( n = 15), S. felis ( n = 10), S. pseudintermedius ( n = 8) und andere Staphylokokken ( n = 6). Es wurden acht verschiedene S. aureus spa‐ Typen identifiziert, die mit humanen klonalen Komplexen assoziiert waren. Eine antimikrobielle Resistenz wurde gegenüber Penicillin (56, 4%), Tetrazyklin (46, 2%), Enrofloxacin (33, 3%), Erythromycin (28, 8%), Amikacin (25, 6%), Clindamycin (23, 1%), Marbofloxacin (15, 4%), Gentamicin (12, 8%), Trimethoprim‐Sulfamethoxazol (10, 3%), Chloramphenicol (7, 7%) und Cefoxitin/Oxacillin (5, 1%) festgestellt. Fünfzehn Isolate (38, 4%) waren multi‐resistent, wobei eine Methicillin‐Resistenz nur mit S. pseudintermedius assoziiert wurde. Schlussfolgerungen und klinische Bedeutung: Diese Ergebnisse bestätigen, dass S. aureus, S. pseudintermedius und S. felis häufig bei einer oberflächlichen Pyodermie bei Katzen auftraten. Semi‐synthetische Penicilline blieben in dieser Studie eine passende Erstlinienbehandlung, wobei die hohe Prävalenz von antimikrobiell‐resistenten Isolaten darauf hinweisen, dass antimikrobielle Empfindlichkeitstests routinemäßig durchgeführt werden sollten. 要約: 背景: 猫では表在性膿皮症は従来からまれな疾患とされ、報告も少ない。特に、アレルギー性皮膚疾患の罹患猫の膿皮症に関連するStaphylococcus属菌に関する研究は不足している。 仮説・目的: 本研究の目的は、(i) アレルギー猫における表在性膿皮症とStaphylococcus属菌との関連性を評価する；(ii) 分離されたブドウ球菌の特徴を把握し、その抗菌剤耐性パターンを解析することであった。 対象動物: イタリアでアレルギー性皮膚炎および表在性膿皮症を持つ猫41頭。 材料と方法: 皮膚スワブを培養し、Staphylococcus属菌を分離した。 種の同定は、マトリックス支援レーザー脱離イオン化質量分析法および16S‐rRNAの配列決定により行った。黄色ブドウ球菌を、スタフィロコッカスプロテインA遺伝子型別によってさらに特徴づけた。抗菌薬感受性はディスク拡散法により測定した。 結果: サンプリングした猫36/41頭からブドウ球菌を分離し、39種類の分離株を同定した。体の部位によってブドウ球菌の種類に偏りがみられた。39株は S. aureus ( n = 15)、 S.felis ( n = 10)、 S. pseudintermedius ( n = 8)およびその他のブドウ球菌( n = 6)であった。ヒトクローナルコンプレックスに関連する8種の黄色ブドウ球菌 spa‐typesを同定した。抗菌薬耐性は、penicillin(56.4%)、tetracycline(46.2%)、enrofloxacin(33.3%)、erythromycin(28.2%)、amikacin(25.6%)、clindamycin(23.1%)、marbofloxacin (15.4%)、gentamicin (12.8%)、trimethoprim‐sulfamethoxazole (10.3%)、chloramphenicol (7.7%)、cefoxitin/oxacillin (5.1%)であった。15株(38.4%)が多剤耐性であったが、メチシリン耐性は S. pseudintermedius のみであった。 結論と臨床的意義: S. aureus 、 S. pseudintermedius および S. felis は、アレルギー猫の表在性膿皮症にしばしば関連することが確認された。本研究では半合成ペニシリン系抗菌薬が第一選択薬として適切であったが、抗菌薬耐性菌が多いことから、抗菌薬感受性試験をルーチンに実施する必要があることが示唆された。 摘要: 背景: 传统上认为猫的浅表性脓皮病罕见，很少有报道。尤其缺乏过敏性皮肤病患猫身上，脓皮病相关的葡萄球菌种类的研究。 假设/目的: (i) 评估过敏猫身上葡萄球菌与浅表脓皮病之间的关系；以及(ii) 表征分离的葡萄球菌，并分析其耐药模式 动物: 意大利41只患有过敏性皮炎和浅表脓皮病的猫。 材料和方法: 皮肤拭子用于分离并培养葡萄球菌。通过基质辅助激光解吸/电离飞行时间质谱和 16S‐rRNA 测序进行物种鉴定。通过葡萄球菌蛋白 A 基因分型进一步表征金黄色葡萄球菌分离株。抗生素敏感性试验采用纸片扩散法。 结果: 从采样的36/41只猫中分离出葡萄球菌，并鉴定出39种不同的分离株。在不同身体部位观察到葡萄球菌属分布不均匀。39株分离株为金黄色葡萄球菌 ( n = 15)、猫葡萄球菌 ( n = 10)、假中间型葡萄球菌 ( n = 8) 和其他葡萄球菌 ( n = 6)。鉴定出8种与人克隆复合体相关的不同金黄色葡萄球菌spa型。抗菌药物耐药情况为青霉素 (56.4%)、四环素 (46.2%)、恩诺沙星 (33.3%)、红霉素 (28.2%)、阿米卡星 (25.6%)、克林霉素 (23.1%)、马波沙星 (15.4%)、庆大霉素 (12.8%)、复方磺胺甲恶唑 (10.3%)、氯霉素 (7.7%) 和头孢西丁/苯唑西林 (5.1%)。15株分离株 (38.4%) 为多耐药而甲氧西林耐药仅与假中间型葡萄球菌有关。 结论和临床相关性: 这些结果证实金黄色葡萄球菌、假中间型葡萄球菌和猫葡萄球菌通常与过敏猫的浅表脓皮病相关。半合成青霉素在本研究中仍然是一种合适的一线治疗方法，但耐药菌株的高流行率表明应定期进行抗生素敏感性试验。 Resumo: Contexto: Em gatos, a piodermite superficial tradicionalmente é considerada rara e há poucos relatos disponíveis. Faltam estudos particularmente a respeito das espécies de Staphylococcus associadas com a piodermite em indivíduos afetados por dermatopatias alérgicas. Hipótese/Objetivos: (i) avaliar a associação entre Staphylococcus spp. e piodermite superficial em gatos alérgicos; e (ii) caracterizar estafilococos isolados e analisar seus perfis de resistência antimicrobiana. Animais: Quarenta gatos com dermatite alérgica e piodermite superficial na Itália. Materiais e métodos: Swabs cutâneos foram cultivados para o isolamento de Staphylococcus spp. A identificação de espécies foi realizada por espectrometria de massas por tempo de voo por dessorção/ionização a laser assistida por matriz e sequenciamento de 16S‐rRNA . Isolados de S. aureus foram posteriormente caracterizados por tipificação genética de proteína A estafilocócica. O teste de suscetibilidade antimicrobiana foi realizado pelo método de difusão em disco. Resultados: Estafilococos foram isolados de 36/41 gatos amostrados e 39 isolados diferentes foram identificados. Observou‐se uma distribuição heterogênea de espécies estafilocócicas nas diferentes áreas corpóreas. Os 39 isolados foram S. aureus ( n  = 15), S. felis ( n  = 10), S. pseudintermedius ( n  = 8) e outros estafilococos ( n  = 6). Oito tipos diferentes de spa de S. aureus associados com complexos clonais humanos foram identificados. Observou‐se resistência antimicrobiana a penicillina (56, 4%), tetraciclina (46, 2%), enrofloxacina (33, 3%), erithromicina (28, 2%), amicacina (25, 6%), clindamicina (23, 1%), marbofloxacina (15, 4%), gentamicina (12, 8%), trimetoprim‐sulfametoxazol (10, 3%), chloramfenicol (7, 7%) and cefoxitina/oxacilina (5, 1%). Quinze isolados (38, 4%) foram multirresistentes enquanto a resistência à meticilina foi associada apenas a S. pseudintermedius. Conclusões e relevância clínica: Esses resultados confirmam que S. aureus, S. pseudintermedius e S. felis são frequentemente associados com piodermite superficial em gatos alérgicos. As penicilinas semi‐sintéticas continuam adequadas como tratamentos de primeira linha neste estudo, mas as altas taxas de resistência antimicrobiana sugerem que os testes de suscetibilidade devem ser feitos rotineiramente.